A review of thalidomide and digestive system related diseases - Xi, Zhao; Jie, Wang; Long, Zou; Shasha, Shi (Frontiers in Oncology, 2025)
Thalidomide, once discovered and used to treat pregnancy sickness, fell out of favor with teratogenicity scandals, and then re-entered the public eye with its amazing efficacy against leprosy and multiple myeloma, and its anti-tumor and anti-inflammatory effects were gradually discovered. In recent years, thalidomide has also begun to gain prominence for its role in digestive disorders, particularly for its anti-angiogenic effects, which are effective in the treatment of dysplastic gastrointestinal hemorrhage. The therapeutic effects of thalidomide in other digestive disorders, including radiation proctitis, inflammatory bowel disease, and malignant tumors of the digestive tract, such as liver, colorectal, gastric, esophageal, and pancreatic cancers, have been proposed in several clinical trials and case reports. Due to its potential adverse effects and controversial clinical utility, it has not been put into clinical use for digestive diseases in large numbers, but its unique therapeutic effects still warrant further study, so this paper analyses and summarizes the use, mechanism of action, and potential therapeutic uses of thalidomide in digestive diseases.